Constructing the Business Case for Gender and Development: Implications on NGO Identity and Legitimacy - McCarthy, Lauren (2010)
Through a case study at Oxfam GB, a large NGO, this study explores the different strategies the organisation is adopting to promote women’s rights in the supply chain and considers the effects such strategies may have on NGOs' identity and legitimacy. Gender is the focus of this thesis since over 70% of the world’s poorest people are women and girls, a disproportionate figure caused largely by discrimination at all levels of society. Business has an enormous part to play in the livelihoods of poor women and girls across the globe. Despite this, corporate attention to the problem has been limited and inconsistent. As Oxfam GB embarks on a new strategy for engaging with corporations on the problem of gender inequality, using a business-case approach, the thesis explores the implications of such terms of reference on NGO identity and legitimacy. Using institutional and organisational theory the study demonstrates how CSR in the form of business/NGO engagement has the power to expand NGO identity and is a component of NGO legitimacy that must be carefully managed.